Anak Usia 17 Tahun Dengan Diabetes Mellitus Tipe 1 dan Disertai Riwayat Penurunan Kesadaran - Febry Caesariyanto Safar; Elly Kusumayati (Lembaga Pengembangan Kinerja Dosen, 2025)
Diabetes mellitus (DM) is a chronic disease with increasing incidence worldwide. This disease not only affects adults, but also children. Diabetes mellitus is characterized by increased blood sugar levels due to impaired insulin production, impaired insulin function, or both. A patient with An. DM came with complaints of shortness of breath and a history of decreased consciousness. The patient also experienced weakness 1 week earlier. From the anamnesis and physical examination, the patient was diagnosed with type 1 DM. Type 1 DM can cause various complications. Children with type 1 DM not only face short-term complications such as hypoglycemia and diabetic ketoacidosis (DKA) which both have significant risks of morbidity and mortality. Children with DKA have life-threatening complications when first diagnosed and are associated with poor metabolic control.